Group music therapy with healthy adult women : an approach for well-being - Eckhaus, Erica (2014)
Research shows that music therapy is often utilized to improve the quality of life of individuals with specified diagnoses; however, the documented information regarding clinical work with healthy adults is limited. The following case study aims to investigate a group music therapy process with healthy adult women. The main objective is to identify implications group music therapy could hold for healthy adult women, such as for the purpose of quality of life improvement and the stimulation of self-actualizing experiences. The study was conducted within a clinical setting where the participants consisted of 4 intentionally selected adult women. The participants attended 12 music therapy sessions that were audio and video recorded. The recordings were utilized for the data analysis, which was qualitative content analysis. The results revealed that group music therapy supports the development of self-actualizing experiences and the improvement of quality of life for healthy adult women. The results also suggest that group music therapy can support the evolution of interpersonal relationships, which can then be related to behaviors, patterns, and beliefs concerning relationships outside of the therapy.